PJMHS 2021
DOI: 10.53350/pjmhs211551074
|View full text |Cite
|
Sign up to set email alerts
|

Gram negative organisms isolated from Blood Cultures and their Susceptibility Pattern

Abstract: Background: Bloodstream infections (BSIs) are an important frequent health problem in terms of their high incidence and lethal outcomes. The bacteria that frequently cause bacteremia are Staphylococcus, Streptococcus, Enterococcus, Escherichia coli, Klebsiella, Enterobacter, Pseudomonas, Neisseria and Haemophilus. Gram negative rods constitute a significant bulk in BSIs. The bloodstream infections due to multidrug resistant pathogens are on the rise globally making treatment more challenging. Aim: To identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This is similar in studies from China, where 59.8% of the isolates were gram-negative bacteria, 40 and Pakistan, 55.7%. 41 However, it was lower than studies from low- and middle-income countries (63.9%), in Egypt (65.3%), and at Kigali, Rwanda (68.3%). 42 44 The sources and numbers of the clinical samples collected, type of infections, types of patients, and geographical differences might be the cause of variation in the overall prevalence of gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This is similar in studies from China, where 59.8% of the isolates were gram-negative bacteria, 40 and Pakistan, 55.7%. 41 However, it was lower than studies from low- and middle-income countries (63.9%), in Egypt (65.3%), and at Kigali, Rwanda (68.3%). 42 44 The sources and numbers of the clinical samples collected, type of infections, types of patients, and geographical differences might be the cause of variation in the overall prevalence of gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 60%
“…51 Similarly, a Pakistan report showed that the isolated gram-negative bacteria exhibited a high resistance rate to cephalosporin, 70% of E.coli , and 80% of Klebsiella pneumoniae . 41 P. aeruginosa , Klebsiella species, and Citrobacter species were 100% resistant to both cefoxitin and cefepime. They were also 50.00–93.33% resistant to ceftazidime and ceftriaxone in our finding.…”
Section: Discussionmentioning
confidence: 99%